Production of benzene/toluene/ethyl benzene/xylene (BTEX) via multiphase catalytic pyrolysis of hazardous waste polyethylene using low cost fly ash synthesized natural catalyst - Gaurh, Pramendra (Waste management (New York, N.Y.), 2018)
Copyright © 2018 Elsevier Ltd. All rights reserved.